Tom and Mot are looking at the functional equation where is differentiable:
After a few minutes of thinking, Tom concludes that for any reals
However, Mot has some doubts. Determine if Tom is right or wrong.
This problem is a part of <Christmas Streak 2017> series .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since f is differentiable, we differentiate both sides with respect to y :
f ′ ( x + y ) = f ′ ( y )
Now we substitute y = 0 :
f ′ ( x ) = f ′ ( 0 )
This suggests that f ′ ( x ) is a constant function.
Integrating both sides, f ( x ) = f ′ ( 0 ) x + C
However, substituting x = y = 0 to the original equation yields f ( 0 ) = 0 , which, substituting x = 0 to the equation above yields C = 0 .
Therefore, f ( x ) = f ′ ( 0 ) x .
f ( x ) = 0 is clearly included, since f ′ ( 0 ) = 0 yields f ( x ) = 0 .